Long Wave Resonance in Tropical Oceans and Implications on Climate: The Pacific Ocean - Pinault, Jean-Louis (Pure and applied geophysics, 2016)
The dynamics of the tropical Pacific can be understood satisfactorily by invoking the coupling between the basin modes of 1-, 4- and 8-year average periods. The annual quasi-stationary wave (QSW) is a first baroclinic-mode, fourth meridional-mode Rossby wave resonantly forced by easterlies. The quadrennial QSW is built up from a first baroclinic-mode Kelvin wave and a first baroclinic-mode, first meridional-mode Rossby wave equatorially trapped and two off-equatorial Rossby waves, their dovetailing forming a resonantly forced wave (RFW). The 8-year period QSW is a replica of the quadrennial QSW for the second-baroclinic mode. The coupling between basin modes results from the merging of modulated currents both in the western part of the North Equatorial Counter Current and along the South Equatorial Current. Consequently, a sub-harmonic mode locking occurs, which means that the average period of QSWs is 1-, 4- and 8-year exactly. The quadrennial sub-harmonic is subject to two modes of forcing. One results from coupling with the annual QSW that produces a Kelvin wave at the origin of transfer of the warm waters from the western part of the basin to the central-eastern Pacific. The other is induced by El Niño and La Niña that self-sustain the sub-harmonic by stimulating the Rossby wave accompanying the westward recession of the QSW at a critical stage of its evolution. The interpretation of ENSO from the coupling of different basin modes allows predicting and estimating the amplitude of El Niño events a few months before they become mature from the accelerations of the geostrophic component of the North Equatorial Counter Current.